Applying life cycle assessment to assess the environmental performance of decentralised versus centralised wastewater systems - Risch, Eva; Boutin, Catherine; Roux, Philippe (Water research (Oxford), 2021)
•Environmental hotspots in decentralised wastewater systems are revealed with LCA•Six wastewater management scenarios are compared using a whole-systems approach•Sewer infrastructures drive mostly centralised scenarios' impacts•No clear conclusions on superior environmental performances of scenarios at endpoint•Boundary conditions under which decentralised scenarios perform better are discussed Decentralised wastewater management (DWM) systems are deployed in areas where the topography does not allow for gravity flow to a centralised system, or requires a complex and expensive pumping station network. Also, DWM systems are often the only option in rural areas where there are no sewage transport networks. This paper aims at addressing the question of the degree to which DWM systems can be considered as viable alternatives from an environmental point of view using the Life Cycle Assessment (LCA) methodology. First, the environmental sustainability is investigated to identify environmental hotspots in two (nature-based and engineered) onsite DWM systems. Second, DWM scenarios are compared against centralised wastewater management (CWM) scenarios using a whole-systems approach. Finally the boundary conditions under which a given DWM scenario performs better than a CWM scenario are discussed. Results show CWM scenarios were less sustainable than DWM scenarios on the resources endpoint due to their sewer infrastructures, however CWM scenarios performed better than DWM scenarios on the ecosystems quality endpoint due to their well-managed air emissions and discharges. While on human health no clear conclusion could be drawn. Finally, for relatively few households (subject of the study in rural areas) CWM scenarios did not score superior performances compared to DWM scenarios on all three endpoint indicators. Yet for a greater number of households it was impossible to decide in favour of decentralisation because of a lack of favourable consensus on all three endpoint indicators. [Display omitted]